ӨМНӨД МОНГОЛЫН ДУНД ЮРЫН УУР АМЬСГАЛ, ГЕОДИНАМИКИЙН НӨХЦӨЛ. I ХЭСЭГ: НАРИЙНСУХАЙТ ОРДЫН ЭЛСЭН ЧУЛУУНЫ ГЕОХИМИЙН СУДАЛГАА - Н., Байгалмаа; Д., Эрдэнэчимэг; Б., Эрдэнэцогт; Л., Жаргал; Т., Огата; Ж., Эрдэнэбаяр; А., Баатархуяг; Д., Нансалмаа; Б., Билгүүн (Geological Issues, 2021)
Middle and Upper Jurassic 18 sandstone core samples from exploration borehole, drilled in Nariinsukhait coal deposit, was studied. Geochemistry of samples indicates that sandstones were derived from acidic and intermediate rocks and mixed with recycled older sedimentary rocks. Possible sources are volcano-sedimentary rocks of Mississippian Tost Formation, granite and granodiorite of Early-Late Carboniferous Tavan-Uul complex and sedimentary rocks of Middle- Upper Triassic Noyon Formation. Paleoclimate indices (C-value, Rb/Sr, Sr/Ba, 1000xRb/K2O and CIA) reflect that coal seams were accumulated in warmer and more humid climate, when paleo-weathering was intense, whereas sandstones were deposited in relatively cold and arid climate. In Late Jurassic, it is more likely that paleoclimate became more arid and cold compared with Middle Jurassic, indicated by quite low CIA and Rb/Sr. Redox condition (Th/U, Ni/Co and V/Cr) was variable, probably controlled by paleoclimate. Moreover, various discrimination diagrams suggested that Middle Jurassic coal-bearing sedimentary rocks were accumulated in foreland basin. It is consistent with previous interpretations of regional tectonic during Triassic and Jurassic time.